The Difficult Diagnosis of Posterior Cortical Atrophy in a 62-Year-Old Woman. (January 2020) - Ziegler, Georg C.; Haarmann, Axel; Daniels, Christine; Herr, Alexandra
Posterior cortical atrophy (PCA) describes a rare heterogenous neurodegenerative syndrome with early visuospatial and visuoperceptual deficits due to atrophy of parieto-occipital brain regions. Here, we describe the case of a 62-year-old woman showing severe cognitive impairments as well as hemianopsia and all core symptoms of Bálint's syndrome. Years ago, the patient had complained about a "tunnel view" and concentration problems. The diagnostic results point to a case of PCA with underlying Alzheimer pathology. The disease course until diagnosis lasted for 7 years, reflecting the diagnostic difficulties with this still largely unknown syndrome. The unfamiliar symptom presentation including fluctuations in cognitive performance, affective symptoms, cerebrospinal fluid (CSF) biomarkers, which were at first inconspicuous, and a former suspected diagnosis of dissociative pseudodementia, altogether brought considerable uncertainty to the involved health-care professionals. We conclude that cases of "atypical dementia" presenting with visual symptoms, even if appearing unspecific at first, are suspect of PCA. This case report provides an ostensive overview of PCA, including imaging data, CSF-findings, original drawings and handwriting samples from the patient.